Respuestas

2014-02-02T12:44:22+01:00
2x-1/5=x/3
6x-3=5x  x=3

3x+4/4
=2x-8/3
9x+12=8x-32
x+44=0
x=-44

-x+4/2-2x+3/6+4x-1/5=x+1/8
(-15x+60-10x-15+24x-6)/30=(x+1)/8
producto de extremos=producto de medios
-120x+480-80x-120+192x-48=30x+30
312-30=30x+8x
282=38x
x=282/38=141/19

-3x+4/2-x+1/3+x+6/5=2-3x/7
(-45x+60-10x-10+6x+36)/30=(2-3x)/7
p.ext=p.med
-315x+420-70x-70+42x+252=60-90x
-315x-70x+42x+90x=60-252+70-420
-253x=-542
x=542/252

-8+x/2=4x-5/6
-48+6x=8x-10
-8x-6x=48-10
-2x=38
x=-19

x/7=2(x+3)/3
3x=14x+42
x=-42/11

x/6=2+ 4x+1/3
3x=12+24x+6
3x-24x=18
-21x=18
x=-18/21=-6/7


14 4 14